The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/biof.1390
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium isoglycyrrhizinate promotes the activated hepatic stellate cells apoptosis via endoplasmic reticulum stress and ameliorates fibrogenesis in vitro and in vivo

Abstract: Varied pathogenetic elements have been touched upon the liver fibrosis, including inflammatory, stress, apoptosis and unfolded proteins aggregation. Magnesium Isoglycyrrhizinate (MgIG) has been accepted to be a neuroprotective effect, hepatoprotective and anti-inflammatory molecule. In our vitro researches, MgIG was considered to activate hepatic stellate cells (HSCs) apoptosis by promoting endoplasmic reticulum stress (ERS) detrimental response to a certain extent. Consequently, MgIG showed its potential ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…TRIzol reagent was used to extract A2780 RNA according to the protocol. Real‐time PCR was executed by 7500 RT‐PCR system as described previously . The mRNA levels of the target genes were calculated and results are from triplicate experiments.…”
Section: Methodsmentioning
confidence: 99%
“…TRIzol reagent was used to extract A2780 RNA according to the protocol. Real‐time PCR was executed by 7500 RT‐PCR system as described previously . The mRNA levels of the target genes were calculated and results are from triplicate experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Cellular senescence is defined as the lack of proliferative potential in cells with irreversible cell cycle status ( Kuilman et al, 2010 ; van Deursen, 2014 ; Fridlyanskaya et al, 2015 ). Since MgIG was previously known for its anti-proliferative effect on HSCs ( Bian et al, 2017 ), we queried if the cells could have acquired replicative senescence. Consistent with Bian et al (2017) , p27 protein expression was found to be increased with MgIG treatment ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Since MgIG was previously known for its anti-proliferative effect on HSCs ( Bian et al, 2017 ), we queried if the cells could have acquired replicative senescence. Consistent with Bian et al (2017) , p27 protein expression was found to be increased with MgIG treatment ( Figure 4A ). However, the increase in p27 was only observable at shorter duration of 24 h, suggesting that senescence is an early process acquired by the cells upon exposure to MgIG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of ER stress and activation of mitochondrial pathways are considered to be the key mechanisms underlying hepatocyte lipoapoptosis . In the present study, we mainly addressed the role of two major protein isoforms of lipin‐1 in the inhibition of steatosis and lipoapoptosis by DHA.…”
Section: Discussionmentioning
confidence: 99%